The UK competition regime : a twenty-year retrospective - Rodger, Barry J.; Whelan, Peter (Lawyer); MacCulloch, Angus (Oxford : Oxford University Press, 2021)
This comprehensive book delves into the UK competition regime since 2000. It critically analyses the current shape of the regime, its past and development, and its future challenges. This book explores both what has gone well and what has not in the past two decades. Academics and practitioners will find this book invaluable.
This edition also issued in print: 2021.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on May 20, 2021).
Keywords: Antitrust law -- Great Britain